Implementasi Model Pembelajaran Problem Based Learning (PBL) untuk Meningkatkan Hasil Belajar IPA Peserta Didik Kelas VII SMPN 1 Plered - Hanifah, Hanifah; Hanikah, Hanikah; Sumiri, Sumiri (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2025)
This study aims to determine the improvement of student learning outcomes through the implementation of the Problem Based Learning (PBL) learning model on the material of Indonesian ecology and biodiversity in class VII of SMPN 1 Plered. The method used is classroom action research (CAR) on class VII E students totaling 35 students who were given treatment using the Problem Based Learning (PBL) learning model. The instrument used was multiple choice questions. Data collection techniques using tests. Data analysis was carried out by comparing the average posttest scores in cycle I and cycle II. Based on the analysis of data obtained in cycle I, students got an average score of 83.71, then in cycle II students got an average score of 84.57. The results of the study indicate that the application of the Problem Based Learning (PBL) learning model can improve the learning outcomes of class VII students of SMPN 1 Plered on the material of Indonesian ecology and biodiversity.